1979
DOI: 10.1016/0022-3115(79)90338-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of first wall damage: Effects of the method of gas implantation

Abstract: Cavity formation in an austenitic alloy of similar composition to type 3(6 stainless steel has been explored with regard to various methods of gas implantation. Irradiations were conducted at 900 K to doses of 1, 10, and 70 dpa with helium injection levels of 20 appm/dpa. Highest swelling (18%) was exhibited by the unimpUnted reference material; a lesser amount by simultaneous helium injection (11%). Greatly reduced swelling due to profuse cavity nucleation was the result of the preinjection of 1400 appm He, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 11 publications
2
21
2
Order By: Relevance
“…The application of NFAs for this purpose is predicated on the ultra-fine-dispersion of nano-scale precipitates distributed throughout the matrix acting as effective nucleation sites for nano-scale He bubbles, rather than the random nucleation of larger He bubbles typically observed in traditional steels that do not contain nano-scale precipitates [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The application of NFAs for this purpose is predicated on the ultra-fine-dispersion of nano-scale precipitates distributed throughout the matrix acting as effective nucleation sites for nano-scale He bubbles, rather than the random nucleation of larger He bubbles typically observed in traditional steels that do not contain nano-scale precipitates [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…As in the current study, Packan and Farrell [132] have found that, for irradiations of an austenitic alloy similar to 316 stainless steel, room-temperature pre-injection of helium followed by 4 MeV ^1++-bombardment to 10 dpa at 898 K caused a reduction in the dislocation density compared to triple-beam ion-irradiation (10 dpa, 200 at.…”
Section: Effect Of Helium and Deuteriummentioning
confidence: 69%
“…According to the critical bubble-to-void and rate theory [19][20][21][22][23], helium facilitates nucleation of voids by lowering the critical radius required for bias-driven void growth, and it usually increases the concentration and reduces the size of voids. Helium encourages the formation of voids and assists swelling, and it is also possible to depress the growth of voids and thereby retarding swelling if voids become the dominant sink [19,20,24,25].…”
Section: Helium Effectmentioning
confidence: 99%
“…Farrell and Packan [19,25] investigated the effects of the method of gas implantation on void formation, including implanting helium at room temperature prior to irradiation, preimplanting helium at the irradiation temperature, and implanting helium during irradiation. They found that the cold-preimplanted helium is much more effective in increasing the void concentration and reducing void size than hot-preimplanted helium and simultaneous implanted helium.…”
Section: Helium Effectmentioning
confidence: 99%